Evaluation of Teacher Digital Competence Frameworks Through Expert Judgement: the Use of the Expert Competence Coefficient - Julio Cabero-Almenara; Rosalía Romero-Tena; Antonio Palacios-Rodríguez (Springer, 2020)
Abstract In this paper, different proposals made by national and international organizations and institutions on Teacher Digital Literacy are taken into account. The 7 most commonly used competence frameworks in international contexts are presented for evaluation through expert judgment. Next, the most suitable for the subsequent realization of a t-MOOC on Teacher Digital Literacy was selected. The selection of these experts was based on seven criteria that helped to establish the expert knowledge coefficient (EKC). This strategy served to obtain the viability of the selected sample. A total of 412 people, 155 experts and 257 non-experts participated in this study. After conducting the expert judgment, in a single round, it was concluded that the European Framework of Digital Competence for Teachers DigCompEdu is the most valued and adequate to be used as reference for the formative t-MOOC, followed by INTEF. This result is logical, since the latter is inspired by the former. These findings do not question the validity of the other competency frameworks, but the preferences granted by the judges.